Perdarahan Saluran Cerna Atas - Darmadi Darmadi; Sania Audry Nasution (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Upper gastrointestinal hemorrhage (PSCA) is bleeding from the lumen of the proximal gastrointestinal tract above the treitz ligament. The causes of PSCA can be classified into variceal bleeding and non-variceal bleeding. The most common causes of upper gastrointestinal bleeding are peptic ulcers, esophageal-gastric variceal veins, ulcerative esophagitis, Mallory-Weiss tears, and bleeding from gastrointestinal vascular lesions. Peptic ulcers are the most common cause of PSCA, accounting for about 50% of cases; the increased incidence is due to nonsteroidal anti-inflammatory drugs (NSAIDs). The Blatchford Score and Clinical Rockall Score are used in patients with non-variceal PSCA to identify the risk of mortality and rebleeding, as well as to triage patients to higher levels of hospital care or immediate endoscopy. Endoscopic examination of PSCA is the chosen way to establish the diagnosis of the cause of bleeding and at the same time useful for performing hemostasis. The top priority in dealing with PSCA hemorrhage cases is the determination of hemodynamic status and resuscitation efforts before establishing a diagnosis or administering other therapies. PSCA therapy is carried out based on the underlying etiology. Patients with variceal bleeding have a worse prognosis than patients with other PSCA etiologies.